Targeted Cell Reprogramming Produces Analgesic Chromaffin-Like Cells from Human Mesenchymal Stem Cells. Issue 12 (December 2013) - Qu, T.; Shi, G.; Ma, K.; Yang, H. N.; Duan, W. M.; Pappas, G. D.
Transplantation of allogeneic adrenal chromaffin cells demonstrated the promise of favorable outcomes for pain relief in patients. However, there is a very limited availability of suitable human adrenal gland tissues, genetically well-matched donors in particular, to serve as grafts. Xenogeneic materials, such as porcine and bovine adrenal chromaffin cells, present problems; for instance, immune rejection and possible pathogenic contamination are potential issues. To overcome these challenges, we have tested the novel approach of cell reprogramming to reprogram human bone marrow (BM)-derived mesenchymal stem cells (hMSCs) using cellular extracts of porcine chromaffin cells. We produced a new type of cell, chromaffin-like cells, generated from the reprogrammed hMSCs, which displayed a significant increase in expression of human preproenkephalin (hPPE), a precursor for enkephalin opioid peptides, compared to the inherent expression of hPPE in naive hMSCs. The resultant chromaffin-like cells not only expressed the key molecular markers of adrenal chromaffin cells, such as tyrosine hydroxylase (TH) and methionine enkephalin (Met-enkephalin), but also secreted opioid peptide Met-enkephalin in culture. In addition, intrathecal injection of chromaffin-like cells in rats produced significant analgesic effects without using immunosuppressants. These results suggest that analgesic chromaffin-like cells can be produced from an individual's own tissue-derived stem cells by targeted cell reprogramming and also that these chromaffin-like cells may serve as potential autografts for chronic pain management.